Implementation of Prayer and Dzikir to Increase Psychological Well-Being in New Students of Al-Jihad Islamic Boarding School Surabaya Carol Ryff's Perspective - Muhammad Mas'udin Difana Putra (Proceedings of Student Symposium on Ushuluddin and Islamic Thought, 2024)
This research aims to examine the implementation of prayer and dhikr and their influence on increasing psychological well-being in new students at the Al-Jihad Islamic Boarding School in Surabaya from Carol Ryff's perspective. The approach used is qualitative with a case study method. Data was collected through in-depth interviews, observation and documentation which was then analyzed thematically. The research results show that the consistent practice of prayer and dhikr can have a positive impact on the Psychological Well-Being components according to Carol Ryff's model, which include self-acceptance, positive relationships with others, autonomy, mastery of the environment, life goals, and personal growth. Students who regularly perform prayer and dhikr report an increase in their ability to manage emotions, develop better social relationships, and have clearer life goals. The implications of this research show the importance of integrating spiritual practices such as prayer and dhikr in mental welfare programs in educational institutions, especially in Islamic boarding schools. This can be an effective strategy to improve the psychological well-being of new students who are adapting to a new and challenging educational environment.